Desenvolvimento de comprimidos contendo pellets revestidos para liberação cólon específica de cetoprofeno - Alencar, Rodrigo Gomes de (2014)
Ketoprofen is a nonsteroidal anti-inflammatory drug used for the treatment of mild to moderate pain in chronic inflammatory conditions. Due to its superior potency ketoprofen can be used in the treatment of inflammatory bowel disease (IBD). The treatment of IBD becomes safer and more effective when the drug is incorporated into colon-specific drug delivery systems. Pellets are multiparticulate solid dosage forms extensively investigated as colon-specific drug delivery systems. Pellets can be introduced into capsules or compressed into tablets. The industrial production of tablets containing pellets has several advantages when compared to the production of capsules. However, the compression of the pellets should not affect the release of the drug and the tablets should quickly disintegrate following administration. Therefore, the aim of this study was to develop tablets containing ketoprofen coated pellets for colon-specific drug release. For this, pellets were produced by extrusion and spheronization technique containing 40% (w / w) ketoprofen. Ketoprofen pellets obtained were coated with two different pH - dependent polymers derived from methacrylic acid (Opadry ® k 94 or Eudragit ® FS 30D) with weight gains of 10 or 20% (w / w). The coated pellets were then compressed under different pellets’ amounts and different compression forces. An extra- granular mixture of lactose and microcrystalline cellulose was used as compression aid. The in vitro release of ketoprofen from the systems obtained was evaluated in Bio Dis ® apparatus. The morphological and physical properties of pellets and tablets were assessed. The Eudragit ® FS 30 D coated pellets with weight gains of 10 or 20% showed higher efficiency of colon-specific delivery (94 %), however, the drug was released slowly and incompletely in conditions mimicking the pH of the colonic region. After compression of the pellets, the efficiency of colon – specific drug delivery was lowered after compression (between 20% and 61%, depending on the formulation). The lowest decrease of colon specific efficiency was observed in formulations containing lower amount of pellets, which also produced disintegrating matrices with potential for use in the topical treatment of IBD.